The profile of Geography teachers from public state schools in Irati – PR (Olhar de Professor, 2011)
Knowledge about teachers´ working context and their interrelations with the personal, economic, social and political aspects contributes to a conscious choice, avoiding future frustrations. The Geography teaching degree at the Universidade Estadual do Centro-Oeste, (State University of the Mid-West), campus of Irati, considers important to go beyond the boundaries of the classroom and know the profile of Geography teachers who work in public state schools in Irati. It is also important to understand some of the characteristics of the profession in terms of content, context and personal expectations of future teachers. The study included a literature reviews and by means of questionnaires it was possible to understand the specific local conditions, allowing the determination of the professional profile of in-service teachers, labor relations and policies related to education, the prospects and difficulties of the career and also the consequences of this context to the teaching-learning relationship.
Keywords: Profile. Teachers. Irati. Geography.